2012
DOI: 10.1111/j.1365-2133.2012.11176.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological clock dysfunction exacerbates contact hypersensitivity in mice

Abstract: The present results suggest that circadian rhythm might be an important factor in the regulation of CHS via corticosterone rhythmicity and/or level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 29 publications
(41 reference statements)
0
40
1
Order By: Relevance
“…This suggests that the mechanisms underlying memory T cell dependent skin inflammatory responses are impaired following loss of CNS circadian rhythmicity. This outcome stands in contrast with a report of enhanced contact hypersensitivity (CHS) responses in Clock -/- mice (Takita et al, 2013). However, plasma corticosterone (B) concentrations are markedly reduced in Clock -/- mice, and effects of this genotype on CHS are eliminated by B or dexamethasone treatment (Takita et al, 2013), suggesting that the immunophenotype is likely mediated by a pleiotropic effect of CLOCK on neuroendocrine function.…”
Section: Discussioncontrasting
confidence: 99%
“…This suggests that the mechanisms underlying memory T cell dependent skin inflammatory responses are impaired following loss of CNS circadian rhythmicity. This outcome stands in contrast with a report of enhanced contact hypersensitivity (CHS) responses in Clock -/- mice (Takita et al, 2013). However, plasma corticosterone (B) concentrations are markedly reduced in Clock -/- mice, and effects of this genotype on CHS are eliminated by B or dexamethasone treatment (Takita et al, 2013), suggesting that the immunophenotype is likely mediated by a pleiotropic effect of CLOCK on neuroendocrine function.…”
Section: Discussioncontrasting
confidence: 99%
“…We have previously shown that Clock Δ19/Δ19 mice exhibit significantly severe levels of allergic contact dermatitis compared with wild-type mice, where the mice were treated with TNCB (2,4,6-trinitro-1-chlorobenzene) on the abdominal skin on day 0 (sensitization) and then with TNCB on the ears on day 5 (challenge) (Takita et al, 2013). The exaggerated allergic contact dermatitis phenotypes in Clock Δ19/Δ19 mice were associated with increased Th2-type responses such as serum IgE levels and mast cell number in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…An intrinsic daily physiological rhythm called circadian rhythm is thought to affect the immune system. Several experimental studies have demonstrated that mutation in the circadian clock genes greatly affects immune responses [104][105][106]. Immune tolerance development is closely associated with the onset of immunological disorders.…”
Section: Circadian Rhythmsmentioning
confidence: 99%